(3GdGSJMhGP hCKQg Ydi GdefGaSI ai GdeYGedGJ GdJLGQjI (B: s (3OQGSI ebGQfI (B/ s - (3MSGe eMeO SjO SYO SQhQ s; (3SGej YHO GdHGbj CHh UGdMs; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb (B- (3LGeYI GdbGgQI,s, 2020)
(3aj Xd GdfXGe GdGbJUGOj GdYGdej GdLOjO GdOGYe dMQjI GdefGaSI hGdJLGQI; CUHMJ GdefGaSI Hjf GdTQcGJ CekQG WHjYkjG heHOkC CSGSkjG aj YGdej GdGbJUGO hGdbGfhf(B: (3haj Xd EOQGc GdTQcGJ dgPg GdJMOjGJ GdLOjOI cGf dRGkeG YdjgG ehGcHJgG HCf JfJgL GSJQGJjLjGJ LOjOI JJfGSH eY GdhJjQI GdeJSGQYI dgPg GdeSJLOGJ(B: (3hCVMi GdGSJMhGP gh GdSHjd GdCeKd dehGLgI eKd gPg GdeJZjQGJ(B: (3hbO JQJH Ydi Pdc EMOGK GdcKjQ ef YedjGJ GdGSJMhGP MJi CNPJ Jdc GdYedjGJ aj GdJUGYO MJi hUdJ Edi CQbGkeG bjGSjI ; MjK hUdJ GdeHGdZ hGdCMLGe Edi eSJhjGJ ZjQ eSHhbI aj hbJfG GdQGgf(B: (3hdbO dhMX Cf GdCKQ GdfGLe Yf Sdhc HYV GdTQcGJ de jcf EjLGHkjG hdG eQZhkHG ajg hHYjO cd GdHYO Yf GdefGaSI GdMQI(B: (3MjK dLCJ GdcKjQ ef Jdc GdTQcGJ Edi YedjGJ GdGSJMhGP ef CLd EMcGe GdSjWQI Ydi GdCShGb GdeYfjI; GdCeQ GdPj ef TCfg JbjO MQjI GdefGaSI YfO ESGAI GSJNOGe gPg GdSjWQI(B.s
(3CWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI, cdjI GdMbhb, bSe GdbGfhf GdJLGQj (B2020.s
(3jTJed Ydi EQLGYGJ HHdjhLQGajI(B: (3UaMI (B501-538.s
(3GdedNU HGddZI GdYQHjIs
Keywords: (3YedjGJ GdHfhcs; (3GdGSJMhGP s; (3GdeYGedGJ GdJLGQjI s; (3GdefGaSI s; (3GdGMJcGQjIs; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdJLGQjs